Analysis of Factors That Influences Customer Retention in Unit Trust Industry - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
ABSTRACT Relationship Marketing has been perceived as an incredible method to fabricate a restrictive long haul relationship with their customers in the present powerful worldwide commercial center. Service quality is becoming increasingly important to a growing number of businesses. A unit trust’s prosperity relies upon the skill and experience of the organization that oversees it. The aim of this research is to emphasise the significance of service quality in unit trust industry. This research was conducted using a questionnaire that was distributed to 200 customers of unit trust agents in Penang. It can be concluded that relationship marketing is essentially corresponded with service quality and consumer loyalty as well as client retention.